Nonlinear behaviour of short elastic cylindrical shells under global bending. (March 2018) - Fajuyitan, O. Kunle; Sadowski, Adam J.; Wadee, M. Ahmer; Rotter, J. Michael
Abstract: A recent computational study identified four distinct domains of stability behaviour at different lengths in thin elastic cylindrical shells under global bending. Cylinders of sufficient length suffer from fully-developed cross-sectional ovalisation and fail by local buckling at a moment very close to the Brazier prediction. Progressively shorter cylinders experience less ovalisation owing to the increasingly strong restraint provided by the boundary at the edges. Very short thin cylinders, however, restrain the formation of even a local buckle and fail through a limit point instability at moments and curvatures significantly in excess of the classical elastic prediction. This limit point behaviour is not caused by ovalisation but by the growth of a destabilising fold on the compressed meridian. The nonlinear behaviour of very short cylinders under global bending is investigated in detail herein, covering a wide range of lengths, radius to thickness ratios and boundary conditions with both restrained and unrestrained meridional rotations corresponding to 'clamped' and 'simply-supported' conditions respectively. Two types of imperfections are investigated, the critical buckling eigenmode and a realistic manufacturing-related 'weld depression'. A complex insensitivity to these imperfections is revealed owing to a pre-buckling stress state dominated by local compatibility bending, and the cylinder length is confirmed as playing a crucial role in governing this behaviour. The study contributes to the characterisation of multi-segment shells with very short individual cylindrical segments, often found in the aerospace and marine industries as well as in specialised civil engineering applications such as LIPP® silos. Highlights: Recent study established four length domains for elastic cylinders under bending. Focus here on short domain with full boundary restraint of local meridional buckling. Short domain exhibits nonlinear equilibrium path not due to Brazier ovalisation. Significantly reduced sensitivity to geometric imperfections revealed. Study of particular significance for analyses of multi-segment or stiffened shells.